Factors Affecting Patients’ Compliance to Metered-Dose Inhaler Drugs in Two Asthma Clinics in Tehran, Iran - Sanaz Tavasoli; Hassan Heidarnazhad; Anooshiravan Kazemnejad (Iranian Journal of Allergy, Asthma and Immunology, 2006)
Asthma affects an estimated 300 million people worldwide. Poor compliance with the prescribed medication leads to increased mortality and morbidity. Various determinants of compliance have been described. The purpose of this study was to determine factors that can influence patients' compliance with prescribed Metered Dose Inhaler drugs. 179 patients with diagnosis of asthma were selected from two asthma clinics in Tehran. 160 of them met the inclusion criteria. Collected data consisted of patients' demographic data, asthma symptoms and severity, medical history of patients and their attitude towards asthma control and using drugs. Compliance was assessed by four questions regarding using Metered Dose Inhaler drugs. There was a significant correlation between compliance and patient's literacy level, attitude about using drugs, and their knowledge about asthma (p=0.012, p=0.0001, p=0.001 respectively). However there was significant negative correlation between symptom control score and compliance (r =-0.270, p=0.004). Other factors including sex, patients' attitude about asthma control and severity of asthma did not show any significant relation. There are four major factors influencing the patients' compliance: level of literacy, attitude towards asthma management, knowledge about asthma, and symptom control. The negative relation between compliance and symptom control may be caused by patients' inadequate knowledge towards continuing treatment after improvement in their conditions. The study emphasizes on the importance of enhancing the patients' compliance. This could be done by providing patients with adequate information about their disease and treatment.